Effective simulation of delamination in aeronautical structures using shells and cohesive elements - Carlos G. Dávila (2008)
A cohesive element for shell analysis is presented. The element can be used to simulate the initiation and growth of delaminations between stacked noncoincident layers of shell elements. The procedure to construct the element accounts for the thickness offset by applying the kinematic relations of shell deformation to transform the stiffness and internal force of a zero-thickness cohesive element such that interfacial continuity between the layers is enforced. The procedure is demonstrated by simulating the response and failure of the mixed-mode bending test and a skin-stiffener debond specimen. In addition, it is shown that stacks of shell elements can be used to create effective models to predict the in-plane and delamination failure modes of thick components. The results indicate that simple shell models can retain many of the necessary predictive attributes of much more complex three-dimensional models while providing the computational efficiency that is necessary for design.